THE IMPLEMENTATION OF WRITE-AROUND PLUS STRATEGY TO IMPROVE STUDENTS’ WRITING SKILL - Muziatun Muziatun; Thalia Miranda Virginia; Ansar Tario Jusuf (English Review: Journal of English Education, 2020)
Writing ability is one of English skills that need to be mastered by students. It is because students must express their idea well in order those readers can easily understand what students write. Moreover, many students’ problems are found in writing such as generating idea, lack of vocabulary, grammatical mistakes and so on. Regarding the occurrence of problem in mostly students’ writing, the researchers want to improve students’ writing skill in descriptive text by implementing write-around plus strategy. The purpose of conducting this research is to investigate whether the implementation of write-around plus strategy can improve students’ writing skill or not. This study is conducted by a pre-experimental study with measurement as the technique of collecting the data and written test as the tool of collecting the data. The research participants were 25 students as the eighth grade students in junior high school SMP Negeri 1 Gorontalo in academic year 2018/2019. The result of this study shows that there were improvements in all writing aspects such as fluency, grammar, vocabulary, content and spelling. The improvements of students’ writing can be shown by data analysis, namely the average result of the research for pre-test got 9.04 score and it currently has been increased in post-test about 13.4 score.